Induction of sexual reproduction and genetic diversity in the cheese fungus Penicillium roqueforti. (20th March 2014) - Ropars, Jeanne; López‐Villavicencio, Manuela; Dupont, Joëlle; Snirc, Alodie; Gillot, Guillaume; Coton, Monika; Jany, Jean‐Luc; Coton, Emmanuel; Giraud, Tatiana
Abstract The emblematic fungus Penicillium roqueforti is used throughout the world as a starter culture in the production of blue‐veined cheeses. Like other industrial filamentous fungi, P. roqueforti was thought to lack a sexual cycle. However, an ability to induce recombination is of great economic and fundamental importance, as it would make it possible to transform and improve industrial strains, promoting the creation of novel phenotypes and eliminating the deleterious mutations that accumulate during clonal propagation. We report here, for the first time, the induction of the sexual structures of P. roqueforti — ascogonia, cleistothecia and ascospores. The progeny of the sexual cycle displayed clear evidence of recombination. We also used the recently published genome sequence for this species to develop microsatellite markers for investigating the footprints of recombination and population structure in a large collection of isolates from around the world and from different environments. Indeed, P. roqueforti also occurs in silage, wood and human‐related environments other than cheese. We found tremendous genetic diversity within P. roqueforti, even within cheese strains and identified six highly differentiated clusters that probably predate the use of this species for cheese production. Screening for phenotypic and metabolic differences between these populations could guide future development strategies.